2008
DOI: 10.1007/s00520-008-0503-4
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of palonosetron compared with granisetron in preventing highly emetogenic chemotherapy-induced vomiting in the Chinese cancer patients: a phase II, multicenter, randomized, double-blind, parallel, comparative clinical trial

Abstract: A single dose (0.25 mg) of palonosetron is not inferior to a single dose (3 mg) of granisetron in preventing CIV and possesses an acceptable safety profile in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…Three studies compared palonosetron with first-generation 5-HT 3 antagonists. 11,14,15 Findings from two larger studies 11,16 suggested that palonosetron provides superior protection against both nausea and vomiting, particularly during the period from 24 to 120 hours after chemotherapy. However, the third study yielded nonsignificant differences, which might be explained by the fact that it was designed as a noninferiority trial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies compared palonosetron with first-generation 5-HT 3 antagonists. 11,14,15 Findings from two larger studies 11,16 suggested that palonosetron provides superior protection against both nausea and vomiting, particularly during the period from 24 to 120 hours after chemotherapy. However, the third study yielded nonsignificant differences, which might be explained by the fact that it was designed as a noninferiority trial.…”
mentioning
confidence: 99%
“…However, the third study yielded nonsignificant differences, which might be explained by the fact that it was designed as a noninferiority trial. 15 These studies were conducted in combined emetic risk populations, but not a non-AC moderately emetogenic population, and compared palonosetron with a first-generation 5-HT 3 receptor antagonist in which dexamethasone has also been included. The preference for palonosetron is an extrapolation from the Saito et al 11 data; when an NK 1 receptor antagonist is not used in the setting of cisplatin and AC chemotherapy, the combination of palonosetron and dexamethasone is superior to granisetron and dexamethasone.…”
mentioning
confidence: 99%
“…Palonosetron, which has pharmacologic and pharmacokinetic advantages over ondansetron with respect to its receptor-binding affinity and half-life [10,12] that appear to translate into significantly improved efficacy in preventing delayed CINV [13,14], is the only 5-HT 3 RA that has been granted US Food and Drug Administration approval for preventing delayed CINV. Positive clinical trial experiences in preventing both acute and delayed CINV have been described for palonosetron alone or with dexamethasone (± other agents) [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In contrast to other 5-HT 3 receptor antagonists, palonosetron exhibits allosteric receptor binding with positive cooperativity and triggers internalization of cell surface serotonin receptor sites [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…13,[16][17][18][19][20] Palonosetron also appears to have an advantageous safety profile compared with ondansetron, granisetron, dolasetron, and tropisetron, which have been associated with electrocardiographic changes and arrhythmias, sometimes leading to the potentially fatal heart rhythm torsades de pointes. 13,14,[21][22][23][24] Palonosetron has been shown not to cause arrhythmias or symptomatic electrocardiographic changes. [25][26][27] The present study was designed to assess the efficacy and safety of two intravenous doses of palonosetron (10 and 20 µg/kg) in paediatric patients with cancer aged from new-born (full term; ≥37 weeks) to <17 years, scheduled to undergo moderately or highly emetogenic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%